Urrets-Zavalia syndrome after implantable Collamer lens placement - Al Habash, Ahmed; Al Arfaj, Khallid; Al Abdulsalam, Omar (Digital Journal of Ophthalmology, 2015)
We describe the case of a healthy 28-year-old woman who underwent implantation of a posterior chamber, phakic, toric, implantable Collamer lens (ICL) in both eyes for correction of bilateral high myopia with astigmatism. On the first postoperative day the patient developed increased intraocular pressure (IOP) and a fixed, mid-dilated pupil in her left eye. The elevated IOP was corrected within 3 days by medical treatment. However, the pupil remained mid-dilated and nonreactive to both light and accommodative effort during 2 months of follow-up; there was no reaction to pilocarpine (0.125% or 4%) eyedrops. The patient was diagnosed with Urrets-Zavalia syndrome (UZS), which has been reported in association with ICL implantation only once previously.